SPECTRAL STUDY OF MITOXANTRONE WATER-SALINE SOLUTIONS (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
Self-association process of mitoxantrone molecules in water-saline solution depending on concentration, temperature and solution ionic strength has been studied. It was shown that in water-saline solutions associates of mitoxantrone molecules are formed and their domination (stacking-like or molecules are bound by hydrogen bonds) strongly depends on not only mitoxantrone concentration, but also temperature and solution ionic strength.
Keywords: mitoxantrone, self-association, water-saline solution, absorption spectrum